HUBUNGAN DAN KONTRIBUSI MOTIVASI BERPRESTASI TERHADAP PRESTASI LOMPAT JAUH SISWA PESERTA EKSTRAKURIKULER PENJASORKES SMP IT AL IKHLAS KOTA PEKANBARU - Armade, Made (Edu Research, 2016)
Based on the result of observation in the field, seen that the Extracurriculler for Student’s of Junior High School of IT Al Ikhlas Pekanbaru City doesn’t operate the practising abiliy yet, so that the Long Jump Achievement result is farly still low. Thepurpose of this research is to explain the relationship and Contribution of the Achievement Motivation the Student’s Long Jump Achievement Student’s Extracurriculler. The reseach result is quantitative by using the corelational analysis technique. The Population of this research were 33 people, while the Samples was taken through Total Sampling, so it were got 33 people. The instrument in the research was used questionnaire for the Achievement Motivation. Data which found was analised using the Simple Corelation analysis technique. Data analysis resultshown that: Achievement Motivation given the contribution, but not significant to the Student’s Long Jump Achievement of the Extracurriculler of Junior High School of IT Al Ikhlas Pekanbaru City, the contribution was 10.24 %.